Episodes of liberalization in autocracies: a new approach to quantitatively studying democratization - Wilson, Matthew Charles; Medzihorsky, Juraj; Maerz, Seraphine F.; Lindenfors, Patrik; Edgell, Amanda B.; Boese-Schlosser, Vanessa; Lindberg, Staffan I. (2022)
This paper introduces a new approach to the quantitative study of democratization. Building on the comparative case-study and large-N literature, it outlines an episode approach that identifies the discrete beginning of a period of political liberalization, traces its progression, and classifies episodes as successful versus different types of failing outcomes, thus avoiding potentially fallacious assumptions of unit homogeneity. We provide a description and analysis of all 383 liberalization episodes from 1900 to 2019, offering new insights on democratic “waves”. We also demonstrate the value of this approach by showing that while several established covariates are valuable for predicting the ultimate outcomes, none explain the onset of a period of liberalization.